Emerging Trends in Beverage Processing - Morata, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Emerging Trends in Beverage Processing describes several non-thermal emerging technologies and biotechnologies. The use of non-thermal technologies represnts the future of food processing because due to the ability of such technologies to increase the shelf life, preserving nutritional and sensory quality. This book considers several promising technologies, such as: hyperbaric storage, ultrasound, high pressure homogeneization, pulsed light, cold plasma and pulsed electric fields, together with other emerging biotechnologies.